2004
DOI: 10.3168/jds.s0022-0302(04)73546-8
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Dairy Yeast Strains for Probiotic Applications

Abstract: To evaluate the potential of yeasts of dairy origin as probiotics, we tested 8 species including Candida humilis, Debaryomyces hansenii, Debaryomyces occidentalis, Kluyveromyces lactis, Kluyveromyces lodderae, Kluyveromyces marxianus, Saccharomyces cerevisiae, and Yarrowia lipolytica, isolated from commercial blue cheese and kefir. Strains were randomly selected from each species and tested for their ability to adhere to human enterocyte-like Caco-2 cells in culture. Among the 8 species, K. lactis showed highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(106 citation statements)
references
References 31 publications
8
91
1
6
Order By: Relevance
“…The adhesive values of HT-29 cells ranging from 2 to 80 were similar to values reported by Kumura et al [12] regarding yeast adhesion to Caco-2 cells.…”
Section: Adhesion Ability To Ht-29 Cellssupporting
confidence: 75%
See 3 more Smart Citations
“…The adhesive values of HT-29 cells ranging from 2 to 80 were similar to values reported by Kumura et al [12] regarding yeast adhesion to Caco-2 cells.…”
Section: Adhesion Ability To Ht-29 Cellssupporting
confidence: 75%
“…Adhesion of probiotic bacteria to the intestinal mucosa is an effective way to exclude pathogens and undesirable bacteria [2,12]. Figure 1 shows the number of yeast cells that adhered to 100 HT-29 cells.…”
Section: Adhesion Ability To Ht-29 Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, Saccharomyces boulardii has been the only yeast commercialized worldwide as a probiotic for humans, but some authors have suggested the use of other yeast species or genera based essentially on in vitro assays and a few clinical trials (Kovacs & Berk, 2000;Kumura et al, 2004;van der Aa Kühle et al, 2005). We demonstrated previously that Saccharomyces cerevisiae strain UFMG 905 has potential as a probiotic due to its ability to protect mice against Salmonella enterica serovar Typhimurium and Clostridium difficile infection in a murine model (Martins et al, 2005), and to inhibit bacterial translocation and modulate both local and systemic immunity of mice (Martins et al, 2007;Generoso et al, 2010).…”
Section: Introductionmentioning
confidence: 99%